Ultrasonic irradiaton of the removal of linear alkylbenzena sulphonates (LAS) from wastewater - Abu Hassan , Mohd. Ariffin; Mantzavinos, Dionissios; Metcalfe, Ian S. (Penerbit UTM Press, 2007)

(untitled)
The effect of low frequency (20 kHz) ultrasonic irradiation on the removal of sodium Linear Alkylbenzene Sulphonates (LAS) from aqueous solutions has been investigated. Sonication of three different initial concentrations of LAS, 500 μgmol/l, 750 μgmol/l and 1000 μgmol/l, were performed. All experiments used a temperature of 30°C, frequency of 20 kHz, power of 125 W, a batch time of 120 min and the pH was left uncontrolled. It was found that the main degradation of LAS at micromolar concentrations proceeded via a reaction with OH· radicals. The initial degradation rate increased with an increase in the surfactant concentration over the whole concentration range studied. The sonolysis of LAS showed a strong inhibition of H2O2 production at a higher concentration. Sonication of LAS in the presence of Br¯ suggested that OH· radicals induced degradation pathway was the dominating sonochemical degradation mechanism.